China–Pakistan Strategic Partnership and Its Impact on Global Power Dynamics - Muhammad Sabil Farooq; Nazia Feroze; Xueying Sun (China Quarterly of International Strategic Studies)
The strategic relationship between China and Pakistan, marked by comprehensive diplomatic, military, and economic collaboration, profoundly impacts global power dynamics. This study examines the developing relationship between China and Pakistan, emphasizing their cooperation within the Shanghai Cooperation Organization (SCO) and its geopolitical ramifications. Utilizing organizations such as the SCO, both countries advance their strategic objectives, with the China–Pakistan Economic Corridor (CPEC) acting as a premier project to increase regional connectivity and economic growth. The authors assess the manner in which the SCO strengthens Sino-Pakistani relations, promotes regional security collaboration, and opposes Western-led coalitions. It also analyzes the partnership’s influence on the U.S.-China competition, India’s strategic apprehensions, and Russia’s involvement in the SCO. This paper examines the problems and opportunities presented by the China–Pakistan alliance, particularly in relation to regional instability and economic interdependence, thereby enhancing the comprehension of how this cooperation influences global power realignment in a multipolar context. The findings underscore the SCOs importance as a strategic platform for both nations, facilitating their navigation of intricate global dynamics and the assertion of their influence internationally.